Dynamic Stretching Increases the Eccentric Rate of Force Development, but Not Jump Height in Female Volleyball Players - Aedo-Munoz, E (Sciendo, 2022)
The present study aimed to analyze the effect of static and dynamic stretching exercises on the rate of force development (RFD) during the eccentric braking phase and jump height in a countermovement jump (CMJ) in female volleyball players. Thirty female volleyball players were randomly distributed in a static stretching (n = 10; SG), a dynamic stretching, and (n = 10; DG) a control group (n = 10; CG). A force plate and a 3D analysis system were employed to detect the eccentric braking phase during the CMJ. The RFD was analyzed in RFD (RFDi) intervals and the accumulated RFD (RFDa), and normalized to body mass. The SG experienced a likely small decrease in the RFDa (mean difference-17.4 N/s/kg) and a likely small decrease in the RFDi (mean difference-19.1 N/s/kg). Contrarily, the DG showed a likely small increase in the RFDa (mean difference 31.2 N/s/kg) and a most likely small increase in the RFDi (mean difference 34.8 N/s/kg). The effect of both static and dynamic stretching on jump height was trivial. Practitioners should consider utilizing dynamic stretching exercises instead of static stretching before a competition in female volleyball players. Further research is needed in order to find complementary strategies during the warm-up that could increase jump height. © 2022 Mauricio Araya-Ibacache, Esteban Aedo-Munõz, Pablo Carrenõ-Ortiz, Christopher Moya-Jofré, Amaya Prat-Luri, Hugo Cerda-Kohler, published by Sciendo.